ANALYSIS OF THE ELASTICITY OF DEMAND FOR PREMIUM RICE COMMODITY WITH SUSNAS DATA: A STUDY ON THE IMPACT OF VALUE-ADDED TAX ON PREMIUM RICE - Vissia Dewi Haptari; Rahadi Nugroho; Ferdinand David Aritonang (SEAN Institute, 2023)
This research aims to determine the elasticity of demand for premium rice, as a study related to the imposition of Value-Added Tax (VAT). The study utilizes provincial panel data for the years 2019 and 2020 processed from the 2019 and 2020 SUSENAS data. The results of the research prove that the demand for premium rice is elastic, with an elasticity of 3.19. When the government imposes taxes on premium rice, the demand will decrease by a larger percentage compared to the price increase. This should also be considered in establishing VAT tariff policies and tax revenue targets from premium rice.